2017
DOI: 10.1038/s41598-017-13687-4
|View full text |Cite
|
Sign up to set email alerts
|

Coherence transformations in single qubit systems

Abstract: We investigate the single qubit transformations under several typical coherence-free operations, such as, incoherent operation (IO), strictly incoherent operation (SIO), physically incoherent operation (PIO), and coherence-preserving operation (CPO). Quantitative connection has been built between IO and SIO in single qubit systems. Moreover, these coherence-free operations have a clear hierarchical relationship in single qubit systems: CPO ⊂ PIO ⊂ SIO=IO. A new and explicit proof for the necessary and sufficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The state conversion problem is important in any resource theory, since it determines the value of states for protocols using the resource under study. The result presented here are a significant generalization of recent results on single-shot coherence theory [10,[23][24][25][26] and single-shot resource theories in general [27], and include necessary conditions on the existence of stochastic conversions, which we generalized to higher dimensions.…”
Section: Discussionmentioning
confidence: 52%
“…The state conversion problem is important in any resource theory, since it determines the value of states for protocols using the resource under study. The result presented here are a significant generalization of recent results on single-shot coherence theory [10,[23][24][25][26] and single-shot resource theories in general [27], and include necessary conditions on the existence of stochastic conversions, which we generalized to higher dimensions.…”
Section: Discussionmentioning
confidence: 52%
“…[9,10]) to the general case of initial mixed states, which is also given in terms of the majorization relation of the corresponding coherence vectors. This result is an step forward on the characterization of conversions between general quantum states under incoherent operations, whose complete solution is only known for the single qubit system [16,17]. Indeed, in higher dimensions (d ≥ 4), it was recently shown that a finite number of conditions in terms of coherence measures are not sufficient to fully characterize coherence transformations on general quantum states [10].…”
Section: Introductionmentioning
confidence: 97%
“…Coherence quantification, and in particular the development of coherence quantifiers which have an operational meaning in experiments, has seen steady active progress within the resource-theoretic framework [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Other important questions concern state transformation, i.e., the possibility to transform a quantum state into another one by using quantum operations which do not create coherence [16,[20][21][22][23][24][25][26][27][28][29][30][31][32]. Coherence theory in multipartite system has also been investigated, allowing to provide powerful links between the theories of entanglement and coherence [13,[33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%